HUBUNGAN KONSUMSI MAKANAN, STATUS GIZI, DAN AKTIFITAS FISIK DENGAN KEPADATAN TULANG (Studi pada Tenaga Kependidikan Fakultas Kesehatan Masyarakat Universitas Diponegoro 2017) - Dyah Sulistyoning Tyas Rahayu; Dina Rahayuning Pangestuti; Siti Fatimah Pradigdo (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Physical activity are at great risk of decreasing bone density. Office workers are among the groups at risk of decreasing bone density due to the assumption of less varied food consumption and low levels of physical activity. The purpose of this study was to determine the relationship between food consumption, nutritional status, and physical activity with bone density of educational staff in Faculty of Public Health Diponegoro University. This research is a type of quantitative research using cross sectional study design. Population in this research counted 78 people and research sample counted 38 people. Sampling technique in this study using simple random sampling. The results showed that bone density with less category (92.1% of respondents), nutritional status with obesity category I (78.9% respondent), energy consumption level with more category (60,5% respondent), carbohydrate consumption level with more category (42,1% respondents), consumption level of protein with light deficit category (55,3% respondent), level of fat consumption with enough category (47,4% respondent), calcium consumption level with moderate deficit category (42,1% respondents), phosphorus consumption rate with severe deficit category (65.8% respondents), frequency of caffeine consumption with rare category (76.3% respondents), and the level of physical activity with light category (92.1% of respondents). Rank Spearman correlation test showed that there was correlation between nutritional status variable with bone density in male respondents (p value = 0.001) while the other four variables (calcium consumption level, phosphorus consumption level, frequency of caffeine consumption and physical activity) were not related to bone density with p value = 0.411, 0.345, 0.561, and 0.632. The result of correlation test on female respondents showed that there were no variables related to bone density with p value = 0,069, 0,570, 0,318, 0,628 and 0,826. This study recommends respondents to eat with variety types of foods and increase physical activity.